2000
DOI: 10.1111/0022-4537.00168
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexism and the Study of Women's Romantic and Friend Relationships

Abstract: The study of women's relationships has been guided by cultural scripts that are deeply heterosexist. In this article, the impact of cultural scripts on the research agenda is explored concerning two aspects of romantic and friend relationships: sexuality and relationship development. Research on lesbians is used to demonstrate how the inclusion of sexual orientation in relationship research challenges heterosexist assumptions and provides new directions for research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 30 publications
0
54
1
Order By: Relevance
“…This includes equality in the division of roles and responsibilities and in terms of relationship maintenance efforts (for a review see Peplau and Fingerhut 2007), and is likely due to same-sex couples' reliance on friendship as the basis for the relationship (e.g., Peplau 1979;Rose 2000;Schwartz 1994). Romance that is based in deep friendship is cooperative, compassionate, synchronous, and close (e.g., Gottman 1998;Rose 2000;Schwartz 1994) and serves the goals of intimacy, deep friendship, and mutual respect (Schwartz 1994).…”
Section: Evidence Of the Friendship Script In Romantic Relationshipsmentioning
confidence: 99%
“…This includes equality in the division of roles and responsibilities and in terms of relationship maintenance efforts (for a review see Peplau and Fingerhut 2007), and is likely due to same-sex couples' reliance on friendship as the basis for the relationship (e.g., Peplau 1979;Rose 2000;Schwartz 1994). Romance that is based in deep friendship is cooperative, compassionate, synchronous, and close (e.g., Gottman 1998;Rose 2000;Schwartz 1994) and serves the goals of intimacy, deep friendship, and mutual respect (Schwartz 1994).…”
Section: Evidence Of the Friendship Script In Romantic Relationshipsmentioning
confidence: 99%
“…Another nine questionnaires were dropped because the participants were homosexual. Desires and opportunities for cross-sex friendship may be affected by sexual orientation (Rose, 2000), and homosexual participants may hold different meanings of gender as compared to their heterosexual counterparts (Feiring, 1999). Of the remaining 413 participants, 22.5% (n = 93) reported having no cross-sex friends.…”
Section: Participantsmentioning
confidence: 99%
“…Friendships enjoy a unique role in the lives of lesbians as they defy traditional heterosexist definitions of friendships (Rose, 2000). For example, Rose and Zand (2000) found that lesbians do not routinely report dating scripts similar to those of heterosexual individuals.…”
mentioning
confidence: 99%